Accountability of Land Deed Officials (PPAT) in Overcoming Duplicate and Overlapping Certificates in Indonesia - Fitra Rahmadani; Fotri Apik Rakhmawati; Noor Hidayah; Tetti Samosir; St. Muslimah Suciati (Faculty of Law, Universitas Pekalongan, 2025)
The formation of the problem of double or overlapping certificates in Indonesia is a crucial issue caused by various factors, such as weak land administration systems, invalid data, lack of physical verification, and inaccurate land boundary mapping. This study aims to analyze the factors that cause double and overlapping land certificates in Indonesia and efforts to provide legal accountability for PPATs related to the existence of double and overlapping land certificates in Indonesia. This study is a juridical-normative study with a conceptual and legislative approach. The results of the study confirm that the Land Deed Making Officer (PPAT) has legal responsibility for errors or violations committed, both in administrative, civil, and criminal aspects. The level of error of PPAT in issuing deeds related to double or overlapping certificates is the basis for determining the form of legal accountability that can be imposed. Therefore, supervision and law enforcement of PPATs are very important to ensure legal certainty and maintain public trust in land transactions.